INTERNATIONAL NETWORKING OF EMPOWER FOUNDATION IN ALLEVIATING HIV/AIDS IN THAILAND - Nudia Vebina Ayumahani (2012)
This thesis tries to explain the effort of EMPOWER Foundation to get International Networking in alleviating HIV/AIDS in Thailand. Thailand known as the most representative country in the world of sex tourism and has a bad record on HIV/AIDS infection. Thailand government was helped by several sector and actor to handle the problem. One of the actor is Non Governmental Organizations (NGOs) such EMPOWER Foundation. EMPOWER Foundation has work field in HIV/AIDS and sex workers term. In tackling th